Daily-level associations between sleep duration and next-day alcohol and cannabis craving and use in young adults. (September 2022) - Graupensperger, Scott; Fairlie, Anne M.; Ramirez, Jason J.; Calhoun, Brian H.; Patrick, Megan E.; Lee, Christine M.
Highlights: Young adults reported stronger craving for alcohol and cannabis on days following relatively shorter sleep duration. Both alcohol craving and use were greater during 14-day bursts of shorter sleep duration, highlighting potential effects of cumulative sleep deficit. Despite effects of sleep duration on next-day cravings, no significant day-level effects were found for actual use of alcohol or cannabis. Abstract: Study objectives: To examine the effects of sleep duration on next-day alcohol and cannabis craving and use among young adults. Method: A community sample of young adults who reported recent simultaneous alcohol and cannabis use at screening ( N = 409; M age = 21.61; 50.9% female) completed twice daily surveys (morning and afternoon) for five 14-day sampling bursts (i.e., 70 days total). Daily measurements included sleep duration, alcohol and cannabis craving, and alcohol and cannabis use (i.e., number of drinks, hours high). Multilevel models enabled examining associations between sleep duration and substance use/craving at three distinct levels: daily-level, burst-level, and person-level. Results: At the day-level, sleep duration was inversely associated with craving for both alcohol and cannabis: Stronger craving was reported on mornings and afternoons after relatively shorter sleep duration. At the burst-level, sleep duration was inversely associated with morning and afternoon alcohol craving indicating stronger alcohol craving, but not cannabis craving, during two-week periods when young adults have accumulated shorter sleep duration. Pertaining to alcohol and cannabis use, no daily-level effects were found, but the burst-level effect showed that participants engaged in greater alcohol use during two-week bursts with shorter sleep duration. Conclusions: Based on a non-clinical sample of young adults reporting substance use, results suggest shorter sleep duration may be a modifiable risk factor as it pertains to substance use and cravings. Results highlight day-level effects of shorter sleep duration on substance use cravings and adverse effects of cumulative sleep deficit on alcohol use.